The Principle Of Inheritance Distribution In Javanese Civil And Customary Law - Imelda Martinelli; Eriyan Rahmadani Dianova; Karen Eklesia Gabriella Kaendo (Asian Journal of Social and Humanities, 2023)
The division of inheritance is an important process that has significant social, economic and cultural impacts. This research aims to conduct a comparative study between the division of inheritance in civil law and Javanese customary law. The focus of this research is to analyze the similarities, differences, and implications of the two legal systems in the context of inheritance division. This research uses a normative juridical research method. In this research, the author refers to the applicable legal aspects to analyze the division of inheritance in civil law and Javanese customary law. The results of this study reveal fundamental differences in the views and practices of inheritance distribution between formal civil law and Javanese customary law which tends to be more traditional and local. Differences include the administrative process, the types of assets that can be inherited, and the role of the family in the division process. This study has the potential to provide a deeper understanding of the interaction between civil law and customary law in the context of inheritance distribution in Java, and identify ways in which these two legal systems can co-exist or integrate more effectively